Application of the PjBL Model Using Big Book Media to Improve Student Learning Outcomes in Indonesian Language Subjects on the Theme of Fable Texts in Grade 2 at SDN Sumberkare 2 - Khusnul Khotimah; Ribut Prastiwi Sriwijayati; Faridahtul Jannah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The instruction of the Indonesian language for primary school kids necessitates teaching approaches and media that align with the developmental features of the students. Initial observations in grade II of SDN Sumberkare 2 revealed that student learning outcomes in fable text materials are inadequate, student engagement and participation in learning are suboptimal, and the learning method remains predominantly teacher-centered. This study seeks to elucidate the implementation of the Project Based Learning (PJBL) paradigm utilizing Big Book media and to assess the enhancement of student learning results in fable text resources. The study used the Classroom Action Research (PTK) methodology, executed in two cycles comprising the stages of planning, action implementation, observation, and reflection. The research participants comprised 15 second-grade pupils from SDN Sumberkare 2. Data collecting methods are executed via observation, testing, and documenting, whilst data analysis employs both quantitative and qualitative methodologies. The study's results indicate that the implementation of the PJBL paradigm with Big Book media enhances student learning outcomes in Indonesian fable text content. The mean score of students rose from 64.8 in the initial cycle to 76.33 in the subsequent cycle, while the learning completeness improved from 33.33% to 100%. Furthermore, students' engagement and involvement in the learning process were enhanced through reading, discussion, puppet creation, and role-playing. The implementation of the PJBL paradigm with Big Book media has demonstrated efficacy in enhancing the academic performance of second-grade students at SDN Sumberkare 2.